Synaptonemal polycomplexes in spermatids: a characteristic trait of Orthoptera? - Wolf, Klaus Werner; Mesa, A. [UNESP] (Springer, 1993)
Spermatogenesis was analysed in a cricket, Eneoptera surinamensis (Gryllidae, Orthoptera), using ultrathin serial sections and transmission electron microscopy. Special attention was placed on documentation of the development and structure of synaptonemal polycomplexes (PCs) within spermatid nuclei. Pachytene spermatocytes showed the usual tripartite synaptonemal complexes in the nuclear lumen. PCs were situated close to chromosomes at the periphery of spindles in prometaphase I spermatocytes, where microtubule density was low. The PCs are probably incorporated into the daughter nuclei of both meiotic divisions by adhesion to chromosomes. Finally, PCs end up within spermatid nuclei. Analysis of serial sections through three nuclei of young spermatids revealed at least one PC within each. The PCs were intimately attached to an electrondense spherical nuclear body. This topographical correlation was confirmed through inspection of random sections. The PCs may have an affinity to the spherical bodies. In more developed spermatids, PCs and nuclear bodies were missing. Disassembly products of the PCs may play a role in spermatid maturation. In a series of other Orthoptera species, PCs have been reported to occur in the cytoplasm or the nuclei of spermatids. In most other systematic groups, PCs do not form at all or disassemble earlier. The presence of PCs in young spermatids, therefore, seems to be typical of Orthoptera.
Keywords: meiosis; pachytene; spermatogenesis; spindle